2017
DOI: 10.1108/pr-08-2016-0214
|View full text |Cite
|
Sign up to set email alerts
|

Innovation programs at the workplace for workers with an intellectual disability

Abstract: Purpose-The purpose of this paper is to examine human resource management (HRM) innovation programs in the early stages of employment for workers with an intellectual disability (WWID). Design/methodology/approach-The first case study was carried out at a large national courier company where a film innovation programme was used to enhance the socialisation process of WWID. The second case study was at a five-star hotel situated in a large city where a buddy system innovation programme was used in the induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
0
17
0
2
Order By: Relevance
“…Looking further into the content analysis of the portfolio articles, several issues can be highlighted (Table 7). Firstly, regarding their specific thematic, some of the papers seem to be focused on workers with disabilities inclusion and human resources practices in the hotel industry (such as [18,19,30,74,75,77,79,81,82] or [84]), taking into account the influence of discrimination and psychological aspects ( [19,30,75,77,78,83] or [86]), others are focused on the customers' perceptions of these workers [80,83,85] or in the managers' perceptions of them [73,76,78,86].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking further into the content analysis of the portfolio articles, several issues can be highlighted (Table 7). Firstly, regarding their specific thematic, some of the papers seem to be focused on workers with disabilities inclusion and human resources practices in the hotel industry (such as [18,19,30,74,75,77,79,81,82] or [84]), taking into account the influence of discrimination and psychological aspects ( [19,30,75,77,78,83] or [86]), others are focused on the customers' perceptions of these workers [80,83,85] or in the managers' perceptions of them [73,76,78,86].…”
Section: Discussionmentioning
confidence: 99%
“…In this article, inclusive HR innovation programs in the early stages of employment of people with intellectual disability are analyzed, using a qualitative case study (also conducting interviews with managers and workers, one focus group, and observations) of two important companies in Australia (one of them is a five-star hotel with a buddy system innovation program used in the induction and training process of this group of people). Thus, it is observed that these innovative programs create opportunities for social inclusion, showing the participants more confidence and independence (highlighting the importance of developing early vocational socialization programs) [84]. 16 USA 2020…”
Section: Australia 2017mentioning
confidence: 99%
“…Det finnes flere eksempler på innovasjon som er av viktighet for eller involverer sektorer for personer med utviklingshemming (Meacham, Cavanagh, Shaw & Bartram, 2017). Forsknings-og innovasjonsprosjekter som involverer personer med utviklingshemming har tradisjonelt vaert gjort på dem, fremfor med dem (se eksempelvis Gauthier-Boudreault, Couture & Gallagher, 2018;Colpani & Homem, 2015;Lanyi & Brown, 2010).…”
Section: Litteraturgjennomgang Innovasjonsprosesserunclassified
“…Recent work has linked human resource management (HRM) and innovation (Meacham et al , 2017). The challenge of HRM seems all the more important in an SME context as human resources have proven to be one of the main obstacles to innovation (Strobel and Kratzer, 2017; Madrid-Guijarro et al , 2009).…”
Section: Introductionmentioning
confidence: 99%